2020
DOI: 10.1016/j.neuropharm.2020.108305
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome inhibition with MCC950 improves insulin sensitivity and inflammation in a mouse model of frontotemporal dementia

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…MCC950, a specific inhibitor of NLRP3 inflammasome activation [ 60 ], has been recently used as a treatment for various NLRP3-related pathological models, including frontotemporal dementia [ 61 ], age-related metabolic syndrome [ 62 ], and obesity-induced insulin resistance [ 23 , 61 ]. Intraperitoneal administration of MCC950 improves glucose tolerance [ 23 , 62 , 63 ], insulin effects [ 61 , 63 ], and the insulin signaling response in skeletal muscle tissue [ 61 ]. Insulin-induced GLUT4 translocation is a critical step in this process [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCC950, a specific inhibitor of NLRP3 inflammasome activation [ 60 ], has been recently used as a treatment for various NLRP3-related pathological models, including frontotemporal dementia [ 61 ], age-related metabolic syndrome [ 62 ], and obesity-induced insulin resistance [ 23 , 61 ]. Intraperitoneal administration of MCC950 improves glucose tolerance [ 23 , 62 , 63 ], insulin effects [ 61 , 63 ], and the insulin signaling response in skeletal muscle tissue [ 61 ]. Insulin-induced GLUT4 translocation is a critical step in this process [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed, for the first time, that MCC950 increases insulin-induced GLUT4 translocation in isolated skeletal muscle fibers from HFD mice. Previous reports have shown that MCC950 treatment improves insulin sensitivity and reduces circulating plasma insulin levels [ 61 , 65 ]. Considering that the model of isolated muscle fibers excludes the influence of other cells, these results suggest that, during IR, the activation of the NLRP3 inflammasome expressed within the skeletal muscle may disrupt the insulin response through an autocrine or paracrine action of the cytokines involved (possibly through IL-1β).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of NLRP3 inhibition has been evaluated mainly in basal conditions, and its effect in an insulinstimulated context remains poorly explored. Additionally, in an animal model of dementia (PLB2 TAU ), glucose homeostasis is altered, displaying inflammation and glucose intolerance [131]. The pharmacological inhibition of NLRP3 improved glycemia management in PLB2 TAU animals, with an increment in InsR (Tyr1162/1163) phosphorylation, increased IRS1 protein levels and reduced JNK phosphorylation levels in the skeletal muscle and liver, showing that NLRP3 could have an active role in the metabolic signaling of insulin target organs [131].…”
Section: Nlrp3 Role In Metabolic Disorders: Limited Information In Skeletal Musclementioning
confidence: 99%
“…Additionally, in an animal model of dementia (PLB2 TAU ), glucose homeostasis is altered, displaying inflammation and glucose intolerance [131]. The pharmacological inhibition of NLRP3 improved glycemia management in PLB2 TAU animals, with an increment in InsR (Tyr1162/1163) phosphorylation, increased IRS1 protein levels and reduced JNK phosphorylation levels in the skeletal muscle and liver, showing that NLRP3 could have an active role in the metabolic signaling of insulin target organs [131]. All these data suggest a link between NLRP3 inflammasome and insulin signaling; however, relevant aspects of this NLRP3 metabolic role such as its influence over glucose uptake and GLUT4 translocation have not been studied in skeletal muscle.…”
Section: Nlrp3 Role In Metabolic Disorders: Limited Information In Skeletal Musclementioning
confidence: 99%
“…Particularly relevant here are immunoreactive Iba-1 (Ionized calcium binding adaptor molecule 1) and GFAP (Glial Fibrillary Acidic Protein) as markers for activated microglia and astrocytes respectively, which occur in close proximity to A deposits [18][19][20]. NLRP3, on the other hand, has shown promise as an experimental therapeutic target [21,22]. Similarly, protein aggregation in AD may be associated with the chronic unfolded protein response, typical for prolonged stress resulting in apoptosis and synaptic loss [15,23].…”
Section: Introductionmentioning
confidence: 99%